POSSIBLE STRENGTH DEFICIT IN SHOULDER ROTATION FOR HYPERMOBILE SWIMMERS. Issue 4 (1st February 2017) - Liaghat, Behnam; Salo, Aki; Juul-Kristensen, Birgit
Abstract : Background: Generalised Joint Hypermobility (GJH) is considered an intrinsic risk factor for shoulder injuries and has a high prevalence in swimmers. Objective: The aim of this study was to investigate the influence of GJH on shoulder muscle strength, muscle activity and muscle fatigue during shoulder rotation movement simulating swimming strokes. Design: Cross-sectional study. Setting: Youth elite sports. Patients (or Participants): 19 elite swimmers with GJH (Beighton's score ≥5 and hypermobile shoulder) were compared to 19 sex- and age-matched control swimmers (Beighton's score ≤3 and no shoulder hypermobility), all 13–17 years. Interventions (or Assessment of Risk Factors): Concentric isokinetic performance in medial rotation (35 ° ) and lateral rotation (60 ° ) was measured at velocities of 60 ° /s (5 repetitions) and 180 ° /s (10 repetitions). Muscle activity during isokinetic testing was measured with surface electromyography from upper trapezius, lower trapezius, serratus anterior, infraspinatus and pectoralis major. Main Outcome Measurements: Peak torque (Nm/BW), total work (J/BW), electromyographic muscle activity (%MVC), and isokinetic and electromyographic fatigue development. Results: In medial rotation at 60 ° /s, there was a significantly lower (14%) total work compared with controls (2.80 vs. 3.26 J/BW; p=0.049), and a tendency to significantly lower peak torque for the GJH group (0.48 vs. 0.55 Nm/BW; p=0.057). There were no group differences in medial rotation at 180 ° /s, or in lateral rotation at both velocities. Muscle activity was non-significantly lower in serratus anterior (range: 27–33%) and pectoralis major (range: 19–26%) in the GJH group in medial rotation. Fatigue development did not differ between groups. Conclusions: Young elite swimmers with GJH displayed decreased medial rotation endurance and strength, which may be potential intrinsic risk factor for development of non-traumatic shoulder injury. These swimmers may benefit from medial rotation endurance and strengthening programs; however, further research is warranted to understand the consequences of such deficits and the corresponding preventive concepts.